Once More on Russian Dialect tyukha-matyukha (tyukha-pantyukha) - L. A. Feoktistova (Научный диалог)
Comprehensive analysis of the widespread in Russian folk dialects idiom tyukha da matyukha and its various variants ( tyukha, pantyukha da kolupay s bratom ; tyukha-matyukha ; tyukha-pantyukha , etc.) is proposed. The author reveals models of phrase-forming, describes the semantics of the idiom and finds out the onomastic status of proper name components. It is emphasized that in structural terms, tyukha-matyukha and tyukha-pantyukha are paired words (names). It is noted that mechanism of reduplication is involved in the creation of enhanced variants of the idiom. The author draws attention to the fact that the semantics of the idiom, among other things, includes an indication of a quantity that varies depending on the interpretation of a dialect speaker of its internal forms: as rhymed “nickname” consisting of a personal name and assessment-describing words, or as a combination of synonyms - appellative characteristics of people similar to each other. It is proved that from the point of view of etymology some phraseological onyms are likely to be appellatives ( matyukha , pantyukha ), while others are personal names, partially exposed appellation forming ( fetyukha , van’ka s man’koy , proshka, yeroshka ). The author points out that among phraseological onyms of both types there can be those which moved from one level of language units to another before joining the expressions ( pantyukha , van’ka s man’koy , proshka, yeroshka ).